miR221/222 in Cancer: Their Role in Tumor Progression and Response to Therapy - Garofalo, M. (2012)
MiRNAs are small non-coding RNAs of ~24 nt that can block mRNA translation and/or negatively regulate its stability. There is a large body of evidence that dysregulation of miRNAs is a hallmark of cancer. miRNAs are often aberrantly expressed and their function is linked to the regulation of oncogenes and/or tumor suppressor genes involved in cell signaling pathway. MiR-221 and miR-222 are two highly homologous microRNAs, whose upregulation has been recently described in several types of human tumors. MiR-221/222 have been considered to act as oncogenes or tumor suppressors, depending on tumor system. Silencing oncomiRs or gene therapy approaches, based on re-expression of miRNAs that are down-regulated in cancer cells, could represent a novel anti-tumor approach for integrated cancer therapy. Here we will review the role of miR-221/222 in cancer progression and their use as prognostic and therapeutic tools in cancer.